Three great characters of the nineteenth century - Jackson, Charles Clifford (My University, 1899)
Introduction: This great century, “with its marvelous Successes, and it’s equally striking Failures,” along intellectual, moral and Social lines is drawing to a close. To our minds it brings thoughts of the wonderful and achievements of man and the problems he has both solved and left unsolved. For the Future he has gathered many facts and laid the foundation for greater progress. More than all others combined, it has lifted mankind to a higher plain and given a clearer view of duties, of privileges and of the methods of progress. While, to a great extent, the commercial spirit has dominated, it has brought to light new phases of character building, and while building for the material and physical, has not altogether omitted thoughts of the ethical. And especially has this been true in this latter half, when there has sprung up new ideals and aspirations in the human breast, pointing toward a soul development, along with the great physical and mental growth.
Citation: Jackson, Charles Clifford. Three great characters of the nineteenth century. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Ninteenth Century Achievements; Character Building; Theses; Manuscripts (documents)